Modification of natural waste clamshells by hydration-dehydration technique for transesterification reaction of palm oil to biodiesel - Mijan, Nurul Asikin (2014)
Utilization of catalyst from waste shell (clamshell) via modification of catalyst via hydration followed by thermal decomposition is not only economic and environmental friendly. The hydration-dehydration method is efficient and easy to manufacture. The clamshell-derived calcium oxide (CS-CaO) from hydration technique shows high basicity as well as high surface area that exhibited higher catalytic activity than CaO of commercial standard. The CS-CaO derived from clamshell was reflux continuously with water for 1,3,6,9 and 12 h and calcined at 600 oC for 3 h to produce heterogeneous catalyst with greater properties (stronger activity and better selectivity relatively due to high surface area and high basicity) that perform better in transesterification reaction. The clamshell was characterized by using X-Ray fluorescence spectroscopy (XRF) and thermogravimetric analysis (TGA). The synthesized catalyst was characterized by using several methods such as X-Ray diffraction (XRD) analysis, N2 adsorption (BET), temperature-programme desorption of carbon-dioxide (TPD-CO2), scanning electron microscopy (SEM). The synthesized biodiesel was characterized using gas chromatography (GC) and atomic absorption (AAS). Furthermore, the catalytic activity of the catalyst derived from clamshell; CS-CaO, CS-CaO 1h, CS-CaO 3h, CS-CaO 6h, CS-CaO 9h and CS-CaO 12h were investigated. Elongating the time during refluxing process in water resulted in high basicity of catalyst and surface area which leads to high catalytic activity (CaO 12h>CaO 9h>CaO 6h>CaO 3h>CaO 1h). The transesterification activity was greatly influenced by basicity of the active sites on the catalyst. The optimization study for palm-based biodiesel production using CS-CaO, CS-CaO 1h, CS-CaO 3h, CS-CaO 6h, CS-CaO 9h and CS-CaO 12h was conducted in this study. The effect of the variables including methanol and oil molar ration (5-17), catalyst loading (0.2-1 wt. %) and reaction time (1-5 h) was investigated. The results shows CS-CaO 9h catalyst resulted in completed reaction (FAME > 98 %) at optimum condition of 2 h reaction time via catalyst loading equal to 1 wt.% with 9:1 methanol and oil molar ratio. Several physicochemical properties of palm-based biodiesel produced was tested and agreed to ASTM D6751 (ASTM D445, ASTM D93, ASTM D97, ASTM D2500) and EN 14214 standard.